Vegetable farming training: modern techniques for high-yield sustainable agriculture - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2024)
Boost your vegetable farming success with expert insights on sustainable practices and innovative techniques. This comprehensive training session teaches how to increase crop yields and improve farm productivity. This video can be a game-changer for farmers, agribusiness professionals, and sustainable agriculture enthusiasts.